2012
DOI: 10.1016/j.jvs.2011.10.132
|View full text |Cite
|
Sign up to set email alerts
|

Blunt abdominal aortic injury

Abstract: This is the largest BAAI series described in the English literature at one institution. BAAIs range from intimal tears to free rupture, with outcomes and management correlating with type and location of injury. Nonoperative management with blood pressure control using β-blockers coupled with antiplatelet therapy and close follow-up is successful in individuals with intimal tears with minimal thrombus formation because they remain stable or resolve on follow-up. Free rupture remains a devastating injury, with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 45 publications
2
44
0
2
Order By: Relevance
“…Based on our results, it appears that these injuries behave similar to aortic injuries in other locations, albeit our sample size was very small. The largest series of nonoperatively managed grade I–II abdominal BAI reported by Shalhub et al (Table V), 14 reported similar findings. Combining these authors’ experience with abdominal BAI and ours, no patients were noted to have injury progression; all patients developed injury regression or have stable injuries on repeat imaging.…”
Section: Discussionsupporting
confidence: 57%
“…Based on our results, it appears that these injuries behave similar to aortic injuries in other locations, albeit our sample size was very small. The largest series of nonoperatively managed grade I–II abdominal BAI reported by Shalhub et al (Table V), 14 reported similar findings. Combining these authors’ experience with abdominal BAI and ours, no patients were noted to have injury progression; all patients developed injury regression or have stable injuries on repeat imaging.…”
Section: Discussionsupporting
confidence: 57%
“…However, abdominal aortic injury has been associated with a mortality rate of 32%. 9,10 Incidence in the pediatric population is even lower and the condition has only been reported in small series and cases. This study is the 22nd case to be reported of blunt abdominal aortic trauma in children less than 16 years of age and just the fourth report of a case of aortic bifurcation rupture found in the literature reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal BTAI accounts for only 2.5-5% of blunt aortic trauma [1,15,16]. The abdominal aorta extends from the diaphragmatic hiatus to the aortic bifurcation.…”
Section: Abdominal Aortamentioning
confidence: 99%
“…Although aortic injury classifications are initially based on thoracic injuries, abdominal injuries can be described with the same classification. Intimal flaps <10mm are safely managed with blood pressure control (B-blockers) and antiplatelet therapy (aspirin) [16,18]. Large intimal flaps, not complicated with thrombosis or arterial insufficiency, are treated with medical management and follow-up CT imaging in 48-72 hours.…”
Section: Abdominal Aortamentioning
confidence: 99%
See 1 more Smart Citation